2013
DOI: 10.1111/een.12037
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition patterns and larval damage by the invasive horse‐chestnut leaf miner Cameraria ohridella on different species of Aesculus

Abstract: Preference–performance relationships are thought to be particularly important for sessile herbivores, such as leaf miners, whose choice of host plant is entirely determined by the ovipositing female. However, this relationship has seldom been examined between a non‐native herbivore and non‐native host plants. Leaf damage and oviposition patterns by the invasive horse‐chestnut leaf miner, Cameraria ohridella Deschka & Dimic, 1986 (Lepidoptera: Gracillariidae), were investigated on 11 different species of Aescul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…ex Camb.) Hook, Aesculus californica (Spach) Nutt., Aesculus parviflora Walter, Aesculus assamica Griff., and Aesculus wilsoni Rehder, which are of Asian and/or of North American origin (Straw and Tilbury 2006;D'Costa et al 2013). Likewise, some species of North American origin (Aesculus sylvatica Bartram, Aesculus pavia L., Aesculus flava Aiton, Aesculus glabra Wild) are colonized by females that deposit eggs on the leaf surface but most larvae die during development (Kenis et al 2003;Ferracini et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ex Camb.) Hook, Aesculus californica (Spach) Nutt., Aesculus parviflora Walter, Aesculus assamica Griff., and Aesculus wilsoni Rehder, which are of Asian and/or of North American origin (Straw and Tilbury 2006;D'Costa et al 2013). Likewise, some species of North American origin (Aesculus sylvatica Bartram, Aesculus pavia L., Aesculus flava Aiton, Aesculus glabra Wild) are colonized by females that deposit eggs on the leaf surface but most larvae die during development (Kenis et al 2003;Ferracini et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…; D'Costa et al. ; Nakadai and Murakami ), which complicates analysis of the ancestral state regarding host use. In addition, individual host plant species cannot be considered as discrete character states because they are phylogenetically nonindependent (Pearse and Altermatt ).…”
Section: Introductionmentioning
confidence: 99%
“…Coding host plant associations at the family or genus level would simplify analysis because methods such as ancestral character state reconstructions are then applicable. However, many herbivorous insects use several closely related plant species (i.e., polyphagy) with varying levels of preference (Smiley 1978;Roininen and Tahvanainen 1989;Thompson 1998;Scheirs et al 2000;D'Costa et al 2013;Nakadai and Murakami 2015), which complicates analysis of the ancestral state regarding host use. In addition, individual host plant species cannot be considered as discrete character states because they are phylogenetically nonindependent (Pearse and Altermatt 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Grabenweger et al (2005) found C. ohridella to be abundant in natural stands of horsechestnut in Greece and Bulgaria, confirmed by Walas et al (2018) for some populations in Greece. Cameraria ohridella shows a preference for A. hippocastanum and the closely related A. turbinata; larval mortality is high on A. carnea (Freise, Heitland, & Sturm, 2003), and other Aesculus species are rarely predated (D'Costa, Koricheva, Straw, & Simmonds, 2013;D'Costa, Simmonds, Straw, Castagneyrol, & Koricheva, 2014;Ferracini, Curir, Dolci, Lanzotti, & Alma, 2010;Freise, Heitland, & Sturm, 2004;Straw & Tilbury, 2006) undoubtedly due to the high saponin levels in the leaves of these other species (Ferracini et al, 2010). The moths will occasionally mine Acer pseudoplatanus and A. platanoides when horse-chestnut is unavailable or as opportunistic infestations near heavily infested horse-chestnuts (Krehan, 1995;Péré, Augustin, Turlings, & Kenis, 2010;Straw & Tilbury, 2006).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%